Power of Ambient Tempurature on the Performance of the Semiconductor Laser - J. S. Ashwin; N. Manoharan (Institute of Advanced Engineering and Science, 2018)
In this paper, the impact of surrounding temperature on the execution of the semiconductor laser is systematically examined in principle. We constructed the recreation display and the simulation results about showed that ambient temperature changes would influence the laser chip temperature, bringing about the laser key parameters in reproduction comes about.